KARAKTERISTIK FISIK KOMPOSIT SABUT KELAPA SEBAGAI INSULATOR PALKA IKAN - Polaris Nasution; Sutopo P. Fitri; Semin ' (Berkala Perikanan Terubuk, 2014)
ABSTRACT Fish catch handling highly influential by the quality of fish that must kept to be fresh. Maintaining the quality of the catch is done with good handling and correctly, especially the storage of fish is highly influenced by the quality of insulation (Insulator). Polyurethane is a solid plastic foam mixture by polyol and Isocynate commonly used as a thermal insulation material on fish hold. Coco fiber derived from coconut fruit seeds contain about 30% of the seed oil. Part of the cross section in the unit cell has a central hollow fibers that serves as an acoustic and thermal insulator so as to decrease the bulk density of the fiber is very well used as an insulator because it has a low thermal conductivity. The addition of coconut fiber as a biodegradable that has a physical properties as a heat insulator aims to minimize use of polyurethane as insulation, addition of Coco fibre can be done until 70%, and the addition of 95.5% density and water absorption reached 26.8%. Ability to absorb water composites increased from 15% to 50.98%, density increased to 5% at 516 kg/m3.Keywords : Coco Fibre, Composite, physical properties, Polyurethane and density